Smoking does not impact social and non-social cognition in patients with first episode psychosis - Sánchez-Gutiérrez, Teresa; García-Portilla, M. Paz; Parellada, Mara; Bobes, Julio; Calvo, Ana; Moreno-Izco, Lucía; ...et al.; Balanza, Vicent (Schizophrenia Research, 2019)
Background: Many studies having shown significant improvements in non-social and social cognitive performance in smoking FEP patients compared to non-smoking FEP patients. The findings are controversial. This study analyzed the effects of tobacco use on non-social and social cognitive function in a large group of FEP patients and a matched healthy control group. Methods: A sample of 335 patients with FEP and 253 healthy controls was divided into four subgroups: control tobacco users (CTU), control non-tobacco users (CNTU), patient tobacco users (PTU) and patient non-tobacco users (PNTU). Demographic variables, tobacco use variables (presence or absence, frequency and duration of tobacco use), neurocognitive (non-social) performance and social cognition were assessed. Results: Comparison of 4 subgroups in non-social cognitive function revealed significant differences after controlling for covariables in executive functions (F = 13.45; p <= 0.001) and working memory domains (F = 4.30; p = 0.005). CTU and CNTU subgroups scored higher in all the domains compared to the PTU and the PNTU subgroups respectively. Social cognitive function was also significantly different within the four subgroups, with control subgroups showing better social cognition than patient subgroups. Significant differences in the executive functions domain were observed when comparing PTU and CTU groups (F = 19.60; p = 0.001). No significant differences were revealed in the comparison between the patient groups. Conclusions: This large study suggests that tobacco use in FEP patients is not related to better non-social or social cognitive performance.
Keywords: tobacco; first episode psychosis; schizophrenia; non-social cognition; neurocognition; social cognition; JCR; Scopus